There's a zombie in my bathtub - Winkler, Henry, 1945- (Winkler, Henry, 1945- Here's Hank ;, 2015)
"With Halloween approaching, Hank and his friends decide to watch a scary movie to get ready for the holiday. But the movie turns out to be a bit too scary for Hank, and suddenly he sees zombies every time he closes his eyes. Everyone says zombies are not real, but then people around him start moaning and acting like the undead, and he is not so sure. Hank is not taking any chances--not when there might be zombies on the loose!"--